2011
DOI: 10.1002/ardp.201000326
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of Novel Rhodanine‐containing Sorafenib Analogs as Potential Antitumor Agents

Abstract: A series of rhodanine-containing sorafenib analogs was designed, synthesized and evaluated for their in-vitro antitumor activity against three cancer cell lines (A549, H460 and HT29). Pharmacological data indicated that some of the target compounds possessed marked antiproliferative activity superior to the reference drug sorafenib, especially the most promising compound 7r (with the IC(50) value of 0.8, 1.3 and 2.8 µM against A549, H460 and HT29 cell lines, respectively). The activity was found to strongly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…For example, 5-isopropylidene-3-ethylrhodanine and 5benzylidene-3-ethylrhodanine demonstrated cytotoxicity towards leukemic cell line CEM by inducing apoptosis [38,274]. Besides this, the modification of known drugs, for example assorafenib, with 5ene-4-thiazolidinone fragments 120 is reported [275,276] (Scheme 56).…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…For example, 5-isopropylidene-3-ethylrhodanine and 5benzylidene-3-ethylrhodanine demonstrated cytotoxicity towards leukemic cell line CEM by inducing apoptosis [38,274]. Besides this, the modification of known drugs, for example assorafenib, with 5ene-4-thiazolidinone fragments 120 is reported [275,276] (Scheme 56).…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…Li et al [33] have synthesized a series of rhodanine-containing sorafenib derivatives. The in vitro pharmacological activity indicated that some of the target compounds possessed high antitumor activity against cancer cell lines, such as A549, H460, and HT29, compared to the standard drug sorafenib.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Rhodanines have been reported to possess antibacterial, antifungal, antiviral, antimalarial, insecticidal, herbicidal, antitumor, anti-inflammatory and cardiotonic activities (6)(7). Besides, rhodanine derivatives are still broadly evaluated for their anticancer activity against different cancer cell lines, often exhibiting selective toxicity against normal cell lines (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%